Towards a new conceptual model for nurses' organizational well‐being: An integrative review. (21st August 2022) - Della Bella, Valerio; Fiorini, Jacopo; Gioiello, Giovanni; Zaghini, Francesco; Sili, Alessandro
Abstract: Aim: The aim of this study is to summarize conceptual models of nurses' organizational well‐being and identify common variables among them. Background: To understand how the characteristics of an organizational context affect workers' well‐being, numerous conceptual models have been developed. Such models have been conceptualized in various working contexts other than health care and not always considering the particularities of the profession of nursing. Evaluation: This integrative review was conducted using the resources of PubMed, CINAHL, Scopus and the Cochrane Library, up until March 2022, and by applying a modified version of Cooper's five‐stage methodology, in accordance with the PRISMA guideline. Key issues: Six reference models focused on different organizational variables and used to evaluate nurses' organizational well‐being were identified: the Effort‐Reward Imbalance (ERI) model; the Job Demands‐Resources (JD‐R) model; the Utriainen et al. model; the Demands‐Resources and Individual‐Effects (DRIVE) model; the Well‐Being, Health‐Promoting Lifestyle and Work Environment Satisfaction (WHS) model and the Nursing Worklife Model (NWM). Conclusion: There is no consensus in the nursing literature on an all‐encompassing conceptual model of nurses' organizational well‐being or on working environment characteristics to be studied or monitored for defining nurses' well‐being. Implications for nursing management: Coming to a consensus on the definition of a nurses' organizational well‐being model and its variables would facilitate nursing management in monitoring and intervening on nurses' work‐life quality and in improving nursing performance and caring outcomes.